Analysis of the expression of putative heat-stress related genes in relation to thermotolerance of cork oak (Journal of Plant Physiology, 2014)
Cork oak (Quercus suber L.) is a research priority in the Mediterranean area and because of cork oaks’ dis- tribution these stands are experiencing daily stress. Based on projections of intensifying climate change and considering the key role of exploring the recovery abilities, cork oak seedlings were subjected to a cumulative temperature increase from 25◦C to 55◦C and subsequent recovery. CO2 assimilation rate, chlorophyll fluorescence, anthocyanins, proline and lipid peroxidation were used to evaluate plant per- formance, while the relative abundance of seven genes encoding for proteins of cork oak with a putative role in thermal/stress regulation (POX1, POX2, HSP10.4, HSP17a.22, CHS, MTL and RBC) was analyzed by qPCR (quantitative Polymerase Chain Reaction). A temperature change to 35◦C showed abundance alterations in the tested genes; at 45◦C, the molecular changes were associated with an antioxidant response, possibly modulated by anthocyanins. At 55◦C, HSP17a.22, MTL and proline accumulation were evident. After recovery, physiological balance was restored, whereas POX1, HSP10.4 and MTL abundances were suggested to be involved in increased thermotolerance. The data presented here are expected to pinpoint some pathways changes occurring during such stress and further recovery in this particular Mediterranean species. ©

Epigenetic and hormonal profile during maturation of Quercus Suber L. somatic embryos. (Journal of plant physiology, 2014)
Somatic embryogenesis is a powerful alternative to conventional mass propagation of Quercus suber L. However, poor quality and incomplete maturation of somatic embryos restrict any application. Given that epigenetic and hormonal control govern many developmental stages, including maturation of zygotic embryos, global DNA methylation and abscisic acid (ABA) were analyzed during development and maturation of cork oak somatic embryos. Our results indicated that development of somatic embryos concurred with a decrease in 5-mdC. In contrast, endogenous ABA content showed a transient increase with a peak in immature E2 embryos denoting the onset of the maturation phase. A cold stratification phase was necessary for embryos to acquire germination ability, which coincided with a significant decrease in 5-mdC and ABA content. Immunohistochemical analyses showed that there was a specific spatial-temporal regulation during embryogenesis, particularly after the cold treatment. The acquisition of germination capacity concurred with a general low 5-mdC signal in the root meristem, while retention of the 5-mdC signal was mainly located in the shoot meristem and provascular tissues. Conversely, ABA immunolocalization was mainly located in the root and shoot apical meristems. Furthermore, a strong decrease in the ABA signal was observed in the root cap after the stratification treatment suggesting a role for the root cap during development of somatic embryos. These results suggest that, in addition to ABA, epigenetic control appears to play an important role for the correct maturation and subsequent germination of cork oak somatic embryos.

Is the Interplay between Epigenetic Markers Related to the Acclimation of Cork Oak Plants to High Temperatures? - Correia, Barbara; Valledor, Luis; Meijón, Mónica; Rodriguez, José Luis; Dias, Maria Celeste; Santos, Conceição; Cañal, Maria Jesus; Rodriguez, Roberto; Pinto, Glória (PLoS ONE, 2013)
Trees necessarily experience changes in temperature, requiring efficient short-term strategies that become crucial in environmental change adaptability. DNA methylation and histone posttranslational modifications have been shown to play a key role in both epigenetic control and plant functional status under stress by controlling the functional state of chromatin and gene expression. Cork oak (Quercus suber L.) is a key stone of the Mediterranean region, growing at temperatures of 45°C. This species was subjected to a cumulative temperature increase from 25°C to 55°C under laboratory conditions in order to test the hypothesis that epigenetic code is related to heat stress tolerance. Electrolyte leakage increased after 35°C, but all plants survived to 55°C. DNA methylation and acetylated histone H3 (AcH3) levels were monitored by HPCE (high performance capillary electrophoresis), MS-RAPD (methylation-sensitive random-amplified polymorphic DNA) and Protein Gel Blot analysis and the spatial distribution of the modifications was assessed using a confocal microscope. DNA methylation analysed by HPCE revealed an increase at 55°C, while MS-RAPD results pointed to dynamic methylation-demethylation patterns over stress. Protein Gel Blot showed the abundance index of AcH3 decreasing from 25°C to 45°C. The immunohistochemical detection of 5-mC (5-methyl-2′-deoxycytidine) and AcH3 came upon the previous results. These results indicate that epigenetic mechanisms such as DNA methylation and histone H3 acetylation have opposite and particular dynamics that can be crucial for the stepwise establishment of this species into such high stress (55°C), allowing its acclimation and survival. This is the first report that assesses epigenetic regulation in order to investigate heat tolerance in forest trees.
The following values have no corresponding Zotero field: publisher: Public Library of Science accession-num: 23326451
Keywords: Acclimatization; Acclimatization: genetics; Acetylation; Blotting; CHROMATIN; CORK oak (citation; Deoxycytidine; Deoxycytidine: analogs & derivatives; Deoxycytidine: metabolism; DNA; DNA methylation; Electrolytes; Electrolytes: metabolism; Epigenesis; Gene expression; Genetic; Genetic Markers; Genome; Heat-Shock Response; Heat-Shock Response: genetics; Histones; Histones: metabolism; Physiological; Physiological: genetics; Plant; Plant Leaves; Plant Leaves: metabolism; Plant: genetics; POST-translational modification; Quercus; Quercus: genetics; Quercus: physiology; Random Amplified Polymorphic DNA Technique; Stress; tags); Temperature; TREES -- Research; Western